A modeling framework for the economic evaluation of baricitinib in moderate-to-severe rheumatoid arthritis. (3rd March 2020) - Schlueter, Max; Rouse, Peter; Pitcher, Ashley; Graham-Clarke, Peita Louise; Nicolay, Claudia; Fakhouri, Walid
ABSTRACT: Objectives : The approval in more than 50 countries of baricitinib, an oral Janus Kinase inhibitor for the treatment of Rheumatoid Arthritis (RA), warrants a framework for corresponding economic evaluations. To develop a comprehensive economic model assessing the cost-effectiveness of baricitinib for the treatment of moderately-to-severely active RA patients in comparison to other relevant treatments, considering the natural history of the disease, real world treatment patterns, and clinical evidence from the baricitinib trials. Methods : A systematic literature review of previously developed models in RA was conducted to inform the model structure, key modeling assumptions and data inputs. Consultations with rheumatologists were undertaken to validate the modeling approach and underlying assumptions. Results : A discrete event simulation model was developed to international best practices with flexibility to assess the cost-effectiveness of baricitinib over a lifetime in a variety of markets. The model incorporates treatment sequencing to adequately reflect treatment pathways in clinical practice. Outcomes assessed include cost and quality-adjusted life years, allowing for a full incremental analysis of cost-effectiveness of competing treatments and treatment sequences. Conclusion : The economic model developed provides a robust framework for future analyses assessing the cost-effectiveness of baricitinib for the treatment of RA in specific country settings.